2022
DOI: 10.1007/s44154-022-00078-7
|View full text |Cite
|
Sign up to set email alerts
|

H3-T6SS of Pseudomonas aeruginosa PA14 contributes to environmental adaptation via secretion of a biofilm-promoting effector

Abstract: Microbial species often occur in complex communities and exhibit intricate synergistic and antagonistic interactions. To avoid predation and compete for favorable niches, bacteria have evolved specialized protein secretion systems. The type VI secretion system (T6SS) is a versatile secretion system widely distributed among Gram-negative bacteria that translocates effectors into target cells or the extracellular milieu via various physiological processes. Pseudomonas aeruginosa is an opportunistic pathogen resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…This may be a general strategy for pathogens to resist acidic conditions (Zhang et al 2013 ). Alternatively, H3-T6SS, which is negatively regulated by OmpR in P. aeruginosa , and its secreted effector protein TepB, were able to aid in bacterial survival under acidic conditions (Yang et al 2022b ).…”
Section: T6ss Confers Resistance To Abiotic Stressesmentioning
confidence: 99%
“…This may be a general strategy for pathogens to resist acidic conditions (Zhang et al 2013 ). Alternatively, H3-T6SS, which is negatively regulated by OmpR in P. aeruginosa , and its secreted effector protein TepB, were able to aid in bacterial survival under acidic conditions (Yang et al 2022b ).…”
Section: T6ss Confers Resistance To Abiotic Stressesmentioning
confidence: 99%
“…Additionally, recent studies have shown effectors that promote biofilm formation, along with proteins encoded within T6SS clusters that mediate adhesion. These proteins may not necessarily be secreted by the T6SS but can still alter the behaviour of T6SS + bacteria [88,89]. These functions benefit T6SS-harbouring organisms by enhancing the effectiveness of the contact-dependent T6 system or by facilitating communication between bacteria that could result in beneficial group behaviours such as protection from predation.…”
Section: Diversity Of T6ss Effectorsmentioning
confidence: 99%
“… P. aeruginosa TepB effector, T 6SS e ffector p romoting b iofilm formation, is involved in the manipulation of bacterial behaviour [89]. This effector is delivered by P.…”
Section: The Membrane Complexmentioning
confidence: 99%
See 2 more Smart Citations